Gender Roles in Coffee Agroforestry Management: A Case Study of the Boritallasa Community Forestry Area, Gowa Regency, Indonesia - Nur Reski; Rahmat Ariandi; Hajawa Hajawa; Hasanuddin Hasanuddin; Sultan Sultan; Andi Azis Abdullah (Forestry Department, University of Muhammadiyah Makassar, 2026)
Agroforestry has been widely recognized as a sustainable land-use system that integrates economic, ecological, and social functions. However, the effectiveness of agroforestry management is influenced not only by biophysical and economic factors but also by gender dynamics that shape labor division, participation, and decision-making within households. This study aimed to analyze gender roles in coffee agroforestry management in the Boritallasa Community Forestry Area (Hutan Kemasyarakatan/HKm Boritallasa), Gowa Regency, South Sulawesi, Indonesia. A case study approach combining descriptive quantitative and qualitative methods was employed. Data were collected from 20 respondents through structured questionnaires, semi-structured interviews, and field observations. Gender roles were analyzed using the Moser Gender Analysis Framework, which classifies activities into productive, reproductive, and community roles, while participation patterns were examined through descriptive statistics and thematic analysis. The results revealed distinct gender-based patterns in coffee agroforestry management. Men were more actively involved in land preparation, planting, and crop maintenance activities, whereas women showed higher participation in harvesting and post-harvest handling. Reproductive activities, including cooking, house cleaning, laundry, and household financial management, were predominantly carried out by women, indicating the persistence of gendered domestic responsibilities. In community-related activities, men participated more frequently in farmer group meetings and collective activities, while women demonstrated increasing involvement in extension and training programs. Decision-making patterns varied according to the type of activity, with men exerting greater influence over technical farming decisions, whereas decisions related to marketing and income utilization were more commonly made jointly by household members. These findings suggest that coffee agroforestry management in the Boritallasa Community Forestry Area is characterized by a complementary division of labor and increasing collaboration in household decision-making. Understanding these gender dynamics is important for designing more inclusive agroforestry and social forestry interventions that recognize the contributions of both women and men and support equitable participation in sustainable resource management.